The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.4236/aar.2013.22009
|View full text |Cite
|
Sign up to set email alerts
|

New antioxidant SkQ1 is an effective protector of rat neural retina under conditions of long-term organotypic cultivation

Abstract: During life human eye is constantly exposed to sunlight and artificial light, the sources of reactive oxygen species (ROS)-the main cause of age-related eye pathology. A novel mitochondria-targeted antioxidant SkQ1 has recently been invented to reduce mitochondrial ROS by cleaning the mitochondria matrix, "the dirtiest place in the cell" in respect of ROS production and accumulation. Earlier we studied SkQ1 effects upon retinal pigment epithelium and choroid in the rat eye posterior cups exposed to long-term 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…In addition, this model as well as approaches using neural retinal explants [24] can be used for screening of new retino and neuroprotectors. For example, the method of organotypic roller cultivation of retina of the rat eye posterior segment has been recently used to study the protective effect of the new antioxidant SkQ1 [25,26] on cells of degenerating retina [27]. In this research, it was shown that very low SkQ1 concentration (20 nM) effectively prevents retinal cell death and main tains cytoarchitectonics of retinal layers, including its ganglion cell layer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this model as well as approaches using neural retinal explants [24] can be used for screening of new retino and neuroprotectors. For example, the method of organotypic roller cultivation of retina of the rat eye posterior segment has been recently used to study the protective effect of the new antioxidant SkQ1 [25,26] on cells of degenerating retina [27]. In this research, it was shown that very low SkQ1 concentration (20 nM) effectively prevents retinal cell death and main tains cytoarchitectonics of retinal layers, including its ganglion cell layer.…”
Section: Discussionmentioning
confidence: 99%
“…Since transplantation of exogenous cellular sources for the retina is not always successful, endogenous stimulation has many advantages. In this regard, the search continues for opportunities to stimulate potential endogenous cellular sources, directing control of the differentiation of cells to restore tissue and the normal functioning of the organ of vision [360][361][362]. Studies show that in damaged neurons of the retina, activation of the transcription program is observed, which promotes initial recovery and partial restoration of function.…”
Section: Pharmacologic Neuroprotection and Activation Of Endogenous Cmentioning
confidence: 99%